2019
DOI: 10.3389/fphar.2019.01003
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Ameliorates Spatial Learning Memory Impairment and Modulates Cholinergic Anti-Inflammatory Pathway in Diabetic Rats

Abstract: Background: Cognitive impairment caused by diabetes has been recognized. Berberine is well known for its resistance to peripheral lesions, but it is rarely used for the treatment of spatial learning and memory caused by diabetes. This study explored the mechanism of berberine to alleviate cognitive impairment via the cholinergic anti-inflammatory and insulin signaling pathways. Methods: Morris water maze was used to appraise spatial learning and memory. Positron-emission tomography (PET) imaging was adopted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 67 publications
(72 reference statements)
2
34
0
Order By: Relevance
“…Of particular interest is to explore the link between peripheral and central insulin signaling and inflammation, and the role of altered cholinergic signaling by age, sex, and disease state (eg, AD and diabetes), including how altered cholinergic signaling may affect inflammation. 35 Another avenue of future research is to examine the link of altered nutritional status in AD, and how nutrition may influence insulin signaling. Finally, there are widespread changes in gene expression in AD postmortem brain in relation to both disease pathology and its clinical expression.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is to explore the link between peripheral and central insulin signaling and inflammation, and the role of altered cholinergic signaling by age, sex, and disease state (eg, AD and diabetes), including how altered cholinergic signaling may affect inflammation. 35 Another avenue of future research is to examine the link of altered nutritional status in AD, and how nutrition may influence insulin signaling. Finally, there are widespread changes in gene expression in AD postmortem brain in relation to both disease pathology and its clinical expression.…”
Section: Discussionmentioning
confidence: 99%
“…Their most active compound was compound 11 (Figure 4) which displayed an increased potency of 3.23-fold over berberine; 1.39-fold over metformin and 1.20-fold over rosiglitazone. Han et al [106] synthesised some carbohydrate-modified berberine derivatives (12) (Figure 4) by assessing cytotoxicity and antidiabetic effect in HepG2 cells. In cytotoxicity assay, the mannose modified berberine derivative showed a potency (IC 50 value) improvement of 1.5 times better than berberine.…”
Section: Synthesis Of Berberine Derivativesmentioning
confidence: 99%
“…Berberine (1, Figure 1) is one of the best characterized natural compounds with diverse pharmacological effects, including anticancer [5][6][7], anti-inflammatory [8,9], cardioprotective [10,11] and enhancement of memory function [12][13][14] effects. Its antidiabetic [15][16][17], antiobesity and anti-hyperlipidaemic [16,18] effects have also been well established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berberine, gypenosides and bifendate are traditional Chinese OTC herbal medicines that possess multiple pharmacological activities like anti-inflammation, anti-oxidant, and anti-tumor [ 8 , 9 , 10 ]. Studies have demonstrated the potential of berberine, gypenosides and bifendate in treatment of interconnected diseases such as diabetes, obesity and cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%